First case of Streptococcus suis bacteremia caused by a serotype 14 strain without pig or pork contact in the Netherlands: A case report - Brizuela, Jaime; Korsten, Koos; van Rossen, Tessel M.; Schultsz, Constance (Diagnostic microbiology and infectious disease, 2025)
•Rare zoonotic S. suis infection without clear transmission route.•First serotype 14 zoonotic infection in the Netherlands.•Divergent European serotype 14 subpopulation. Streptococcus suis is a porcine pathogen that causes severe zoonotic infections in humans resulting in meningitis and sepsis. The main risk factors for S. suis zoonotic infections are consumption of raw pork products and direct contact with live pigs or pork, in particular in the presence of skin injuries. Most human infections are caused by clonal complex 1 (CC1) serotype 2 isolates. We describe an unusual case of S. suis bacteraemia caused by a CC1 strain carrying a serotype 14 capsule in a patient without a history of consumption of raw pork products or contact with either pig or pork. The isolate formed a serotype 14 clade with three German serotype 14 strains that has diverged from the main CC1 serotype 2 lineage. This is the first report of a human infection caused by a serotype 14 S. suis in the Netherlands, which in combination with its unknown transmission route and severity of the disease, calls for its notification.